THE SPIRITUAL AUTOBIOGRAPHY OF CHARLES DE FOUCAULD - JEAN-FRANCOIS SIX (Ijamsville, Maryland The Word Among Us Press, 2003)
Charles de Foucauld was known in Paris for his wild parties and self-indulgent lifestyle. However, after his conversion in 1886 at the age of twenty-eight, his youthful excesses were replaced by devotion to Jesus, love for the Eucharist, and a thirst for souls. He spent three years in the Holy Land as a hermit, was ordained a priest, and then traveled to the Sahara Desert in Africa $1 (Bwhich he had explored in his younger days $1 (Bto live among the poor and spread the gospel of love. He was martyred by Muslim gunmen in 1916. The Spiritual Autobiography of Charles de Foucauld reveals this holy man's intense desire to imitate Jesus while growing closer to him each day.s